Physical model experiment on the influence of water depth on the underwater pipeline surface impacted by landslide surge - Hong Ji (Nature Portfolio, 2021)
Abstract A physical model experiment of flume block landslide was used to study the influence of landslide surge impact on underwater pipeline surface under different water depths. The influence of surge impact pressure on pipelines with different water depths and the impact pressure of surge at different angles of underwater pipelines wall were analyzed. And the relationship between the maximum impact pressure of underwater pipelines and the depth of water was obtained. The results indicated that with the decrease of the water depths, the maximum impact pressure at the wall of the underwater pipeline increases approximately linearly, and the slider is easier to form higher first wave height. The maximum impact pressure of the upper surface of the pipeline wall is greater than that of the lower surface of the pipeline wall under the same working conditions. It is also found that the smaller the depth of water, the larger the maximum pressure and average pressure at the measuring point would be and the greater the pressure fluctuation becomes when slider volume and landslide water inlet angle and speed remain the same.